Screen Time vs. Active Play: How Digital Exposure Impacts the Acquisition of Fundamental Motor Skills in Early Childhood - Maria, Ilga; Puteh, Mada-o (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study investigated the impact of daily recreational screen time and active play on the acquisition of fundamental motor skills (FMS) in preschool children in Indonesia. This study aimed to address the regional evidence gap in digital exposure and motor development.Design/methods/approach – This study investigated the impact of daily recreational screen time and active play on the acquisition of fundamental motor skills (FMS) in preschool children in Indonesia. This study aimed to address the regional evidence gap in digital exposure and motor development. A quantitative cross-sectional design with a comparative approach was used to study 120 children aged 4–6 years (57% girls) enrolled in eight kindergartens in Yogyakarta. Parents completed a validated 7-day home screen usage diary. Data collection techniques used an Observation Sheet during active play during school breaks, and a questionnaire to administer the Gross Motor Development Test-3. Analysis techniques used a multiple regression model controlling for age, gender, body mass index, and household socioeconomic status; mediation was tested with PROCESS v4.3.Findings – Average screen exposure was 114 min day¹ (SD = 46), with 42 % of children exceeding the 2 h guideline. High-screen users scored significantly lower on locomotor (M = 27.1 vs. 31.3) and object-control (M = 25.8 vs. 29.5) domains (p < .01). Each additional 30 min of active play predicted a 2.1-point increase in composite FMS (β = .34, p < .001) and partially mediated the negative screen-time effect (indirect β = –.09, 95 % CI = –.15 to –.04). Overall, screen time accounted for 18 % of the variance in FMS after covariate adjustment.Research implications/limitations – The cross-sectional approach cannot infer causality, and parent-reported diaries may under- or overestimate actual screen exposureChildcare policies should embed structured motor sessions and favour interactive, movement‑rich media over passive content.Practical implications – Early-childhood educators and health professionals should prioritise daily active-play opportunities and counsel families to limit recreational screens to <1 h day¹. Integrating motor-rich play modules into kindergarten curricula could mitigate digital-time trade-offs.Originality/value – This is the first Indonesian study to quantify the concurrent effects of screen use and active play on objectively measured FMS. The findings extend global evidence into a culturally specific context and highlight active play as a protective factor that can offset, but not fully negate, the detrimental motor effects of excessive screen exposure.Paper type Research paper